1978
DOI: 10.1063/1.325370
|View full text |Cite
|
Sign up to set email alerts
|

Resistivity and microstructure of polycrystalline Au films deposited by rf bias-diode and triode sputtering

Abstract: Two different sputtering deposition methods, rf bias-diode and triode sputtering, were used to prepare highly polycrystalline films with mean crystallite size between 38 and 85 Å. The bias-sputtered films were metallically conductive at 20 Å nominal film thickness and had a large component of electrical resistivity independent of temperature. Films prepared with more than 5% rf bias had atomically roughened surfaces that showed completely diffused surface scattering. The reflection coefficient for grain-bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Detailed modeling of the conductivity of sputtered gold is difficult without knowing its polycrystalline structure. However, previous work [35] suggests that the conductivity of a 20 nm sputtered gold film will be 5-10 orders of magnitude less than that of the bulk metal, which has a typical conductivity of 4.5-5.0 × 10 7 S m -1…”
Section: Methodsmentioning
confidence: 97%
“…Detailed modeling of the conductivity of sputtered gold is difficult without knowing its polycrystalline structure. However, previous work [35] suggests that the conductivity of a 20 nm sputtered gold film will be 5-10 orders of magnitude less than that of the bulk metal, which has a typical conductivity of 4.5-5.0 × 10 7 S m -1…”
Section: Methodsmentioning
confidence: 97%
“…REVUE DE PHYSIQUE APPLIQUÉE TOME 1. Introduction. -In the recent years it has been observed that evaporated [1][2][3][4] and sputtered [5][6][7][8][9] thin metal films exhibit a fine grained structure and thus grain-boundary scattering can significantly dominates the electromechanical properties of these films [10][11][12][13]. Mayadas and Shatzkes [14] have taken into account the grain boundary scattering and have proposed a conduction model [14] which describes the combined effects of grain-boundary, external surfaces and background scatterings.…”
mentioning
confidence: 99%